Transmitting Traditions: Devolving Values across Generations - Bhattarai, Tikaram (Janajyoti Journal, 2025)
This study examines and explore how living values respect and cooperation in particular devolve throughout time, with an emphasis on how these values change in contemporary societies. The study uses narrative inquiry to investigate how cooperation and respect are passed down from older to younger generations, as well as how these values change as a result of social norm changes, cultural upheavals, and technological improvements. The results show that respect once an absolute, culturally set value has evolved into something more situational and context-dependent, showing a move away from customary, group-based behaviors and toward more customized, flexible interpretations. In a similar vein, cooperation has evolved from an unconditional means of ensuring one's own survival to a more conditional, self-serving exchange. The alterations in daily encounters are ascribed to wider cultural patterns including industrialization, financial strains, and the emergence of technological instruments. The study's findings support theories like Maslow's Need Theory and Durkheim's Social Integration Theory, which contend that changing values are a reflection of both societal and individual adjustments to contemporary living. Understanding how traditional values are upheld, modified, or changed in the face of generational and societal transitions is aided by this research.